Co-existence of benign gynecological tumors with endometriosis in a group of 1,000 women - Matalliotaki, Charoula (Oncol Lett, 2018)
The purpose of this study was two-fold, first to investigate the association between endometriosis and the risk of benign gynecologic tumors and, secondly, to evaluate the distribution of endometrioma and ovarian cysts in women with endometriosis. The medical and pathological reports of 1,000 women with endometriosis were retrospectively reviewed. The incidence of ovarian cysts, uterine leiomyomas and adenomyosis, as well as the side of ovarian cysts were further compared. A total of 295 cases of endometriomas, 172 cases of adenomyosis, 173 cases of ovarian cysts and 89 cases of uterine leiomyomas were confirmed histologically in patients with endometriosis. Serous cysts represented the most frequent diagnosis (n=81, 8.1%) in women with ovarian cysts, followed by dermoid cysts (n=15, 1.2%). In women with unilateral endometriomas, the observed proportion of left-sided cysts was found in 65.6% (164 of 250), significantly higher compared with right-sided cysts (86 out of 250, 34.4%) (P<0.001). Moreover, patients with other ovarian cysts were recognized as left-sided in 60% (96 out of 160) of cases, significantly higher compared with right-sided cysts (64 out of 160, 40%) (P<0.01). On the whole, the current study indicates that endometriosis may be associated with an increased risk of benign gynecological tumors, such as ovarian cysts, adenomyosis and leiomyomas. The results of this study confirm a left lateral predisposition of endometriomas and ovarian cysts.